Spatio-Temporal Differentiation Characteristic and Evolution Process of Meteorological Drought in Northwest China From 1960 to 2018 - Li, Hui; Hou, Enke; Deng, Jiawei (Frontiers in Earth Science, 2022)
Under the background of global climate change, the response characteristic of meteorological drought is of great concern, especially in the arid or semi-arid regions. By employing the Standardized Precipitation Index (SPI), TPFW-MK test, Run Theory, Moran’s I and General G, the spatial-temporal dynamic evolution process and spatial similarity of drought were clarified based on the meteorological data from 122 stations in Northwest China (NWC) during 1960 to 2018. The results indicated that the drought situation of NWC was lightening regardless of annual or seasonal scale. According to the Z-statistics by TPFW-MK test, there existed an obvious wet trend in west NWC and a slight dry trend in east NWC. The migration pattern of the gravity center of SPI revealed that the drought shifted generally towards low latitudes over last decades, there was a northwest (1960-1990) and northeast (1990-2018) variation in the covering shapes of the standard deviational ellipses of SPI. Meanwhile, the distribution pattern of drought characteristics suggested that more droughts occurred in east of NWC which were less harmful while fewer droughts happened in west NWC which were with greater drought damage.The results of GMI indicated that both annual and seasonal drought variables were characterized with significant spaital autocorrelation, the spatial distribution of winter drought variables was more disperse than other seasons while the damage of summer and autumn drought were bigger than that in spring and winter. Besides, the results of LMI showed that there was obvious agglomeration in the overall distribution of drought variables, which were with strong spatial polarization effect. The hot spots of drought frequency mainly distributed in Shaanxi, while the hot spot and sub hot spots of drought duration and severity were concentrated in northwest Xinjiang, indicating the Shaanxi Province and its surrounding areas have similar drought conditions (more droughts, shorter duration and lower severiy) while northwest Xinjiang and adjacent areas were characterized with fewer droughts but longer duration and higher severity. The results of revealing the drought development process and identifying the location of drought aggregation will provide references for supporting climate adaptation strategies and preventing drought-related loss.